Au son d’un savoir impossible : Bouvard et Pécuchet à la télévision, avec la musique de Michel Portal - Dario Cecchi (Flaubert: Revue Critique et Génétique)
The article is concerned with the filmic adaptation, for the French television, of Bouvard et Pécuchet. This adaptation was realized by Jean-Daniel Verhaeghe in 1989, being based on Jean-Claude Carrière’s script and with the music composed by Michel Portal. This music is the principal object of this article. The method used to analyze the role played by music and sound in the montage of this adaptation is borrowed from aesthetics. In particular, the article argues that Portal’s work does not follow the idea of an ‘harmonious’ intertwining between pictures and sound theorized and practiced by Eisenstein in his theoretical writings, as well as in his movies. On the contrary, Portal works at realizing a sound dimension that affects the spectator with the incommensurability between the ideal of total knowledge characterizing Flaubert’s characters and their actual ‘idiocy’ in the realization of this ideal. As a consequence, it is a montage concerned more with the sublime, in Kant’s acceptation, than with beauty and harmony.